Perception of medical interns and residents about specialty of microbiology and the role of microbiologists during COVID-19 pandemic - Khan, Imran Ahmed; Singh, Amresh Kumar; Zaman, Kamran; Shrivastava, D. K. (International Journal of Research in Medical Sciences, 2021)
Background: The speciality of microbiology is closely associated with keeping people healthy and disease free by accurate diagnosis of infectious diseases. In spite of this, awareness about the speciality seems to be scarce. In the present scenario, public perception about microbiology has been changed a lot. The SARS-CoV-2 pandemic has highlighted the crucial role of microbiologists in the health care system. The aim of this survey was to determine the perceptions of medical interns and residents regarding the specialty of microbiology and the role of microbiologists in maintaining and promoting health of people. Methods: On-line survey using google form to identify perception of medical interns and residents about the speciality of microbiology. Results: A total 298 valid responses were obtained response rate 26.02% from the participants among them 167 (56.0%) were male and 131 (44.0%) females. Though, the attitude of medical interns and residents were found positive for the speciality of microbiology, they even recognize the importance of medical microbiology in their future role as medical practitioners, but only few (3.48%) wished to opt it as their career. Conclusions: The risks and responsibilities of a microbiologist involved in managing patients seldom get due acknowledgement. Adequate measures need to be taken to enlighten the authorities about microbiology and various responsibilities of microbiologists. The health care providers and medical teachers needed to appreciate the perception of young medical students regarding current and future trends in specialty choice and take concrete steps to meet the unmet need of health care.